Design and Simulation of a Hybrid Wind/Solar/Diesel/ Battery Off-Grid System for Rural Areas: A case Study in Al-Mahmudiyah Tribal Zone of Iraq - Amal T. Mawlood; Ibrahim Ismael Hamarash (Zanco Journal of Pure and Applied Sciences, 2023)
This paper details a framework for designing appropriate hybrid power supply system for a tiny and remote off-grid rural locations. A combination of Solar PV/Wind turbine/Diesel generator have been simulated and tested in different cases. The optimization program 'Hybrid Optimization Model for Electric Renewables' HOMER is utilized in this study to discover the best architecture. Data from load forecast together with the solar/wind international atlases have been used in the design. The total net present cost NPC and levelized cost of energy COE have been minimized to pick an economically practical and technically capable off-grid hybrid power system. The simulated study showed that the solar generator offers the most assistance for power generation, accounting for around 77.3%, while wind accounts for approximately 19%. Also, the overall net present cost (NPC) is 225,574.87, and the cost of electricity (COE) scheme is as low as 0.4037 per kWh.